Covalent cannabinoid receptor ligands – structural insight and selectivity challenges. Issue 5 (11th April 2022) - Liddle, Ian; Glass, Michelle; Tyndall, Joel D. A.; Vernall, Andrea J.
Abstract : X-ray crystallography and cryogenic electronic microscopy have provided significant advancement in the knowledge of GPCR structure and have allowed the rational design of covalent GPCR ligands. Abstract : X-ray crystallography and cryogenic electronic microscopy have provided significant advancement in the knowledge of GPCR structure and have allowed the rational design of GPCR ligands. The class A GPCRs cannabinoid receptor type 1 and type 2 are implicated in many pathophysiological processes and thus rational design of drug and tool compounds is of great interest. Recent structural insight into cannabinoid receptors has already led to a greater understanding of ligand binding sites and receptor residues that likely contribute to ligand selectivity. Herein, classes of heterocyclic covalent cannabinoid receptor ligands are reviewed in light of the recent advances in structural knowledge of cannabinoid receptors, with particular discussion regarding covalent ligand selectivity and rationale design.